(untitled) (Global Journal of Human-Social Science, 2024)
With the Russian military aggression against Ukraine which was launched on 24 February 2022 as a special military operation Russia essentially wants to prevent Ukraine from joining the Western world to which Hungary belongs As there are one and a half hundred thousand Hungarians living in Ukraine it is in the fundamental Hungarian national interest that Ukraine succeeds in its efforts to join the Western integration organizations Everyone agrees that armed intervention against a sovereign state without a declaration of war is a violation of international law and constitutes aggression regardless of the motives However in order to judge the Russia-Ukraine war objectively it should be mentioned that since 1945 not only the Soviet Union and its successor the Russian Federation but also the United States of America have made use of this illegitimate instrument under international law and the UN Charter on numerous occasions It is also hard to deny that interventions have always been and are always driven by the violent defence of a great power s sphere of influence or by a desire to expand its sphere of interest or by some other interest considered legitimate and just which does not exempt the intervening power from condemnation under international law for the use of brute force and its consequences